Peran Guru Dalam Menanamkan Budaya Disiplin Untuk Pembentukan Karakter Peserta Didik Di SMP Santa Maria Maumere - Rikardus Riin; Nurdin H. Abd. Rahman; Mohammad Fitri (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
This study aims to determine the teacher's role in instilling a culture of disciplinefor students at Santa Maria Maumere Middle Schooland to find outwhat factorscause the low level of discipline among students at Santa Maria Maumere MiddleSchool. Thisstudy uses a qualitative method that is ddescriptive. The informants inthis study were school principals, civics teachers and student teachers at SMPSanta Maria Maumere. The data collection techniques used were observation,interviews and documentation. Data analysis techniques were in the form of acollection, data reduction, and drawing conclusions or verification. The resultsshowed that: The role of the teacher in shaping the discipline culture of students atSanta Maria Maumere Middle School, namely the teachers at Santa MariaMaumere Middle School must have a good attitude, the teacher is able providemotivation that can shape the positive character of students, teachers are expectedto provide students with an understanding of morals, as well as teachers guidingtdents in student council and extracurricular activities. While the factors that influence the low discipline culture of students at Santa Maria Maumere MiddleSchool are Heredity Factors and Environmental Factors